Direct Observation of Aggregation‐Induced Emission Mechanism. (22nd June 2020) - Guan, Jianxin; Wei, Rong; Prlj, Antonio; Peng, Jie; Lin, Kun‐Han; Liu, Jitian; Han, Han; Corminboeuf, Clémence; Zhao, Dahui; Yu, Zhihao; Zheng, Junrong
Abstract: The mechanism of aggregation‐induced emission, which overcomes the common aggregation‐caused quenching problem in organic optoelectronics, is revealed by monitoring the real time structural evolution and dynamics of electronic excited state with frequency and polarization resolved ultrafast UV/IR spectroscopy and theoretical calculations. The formation of Woodward–Hoffmann cyclic intermediates upon ultraviolet excitation is observed in dilute solutions of tetraphenylethylene and its derivatives but not in their respective solid. The ultrafast cyclization provides an efficient nonradiative relaxation pathway through crossing a conical intersection. Without such a reaction mechanism, the electronic excitation is preserved in the molecular solids and the molecule fluoresces efficiently, aided by the very slow intermolecular charge and energy transfers due to the well separated molecular packing arrangement. The mechanisms can be general for tuning the properties of chromophores in different phases for various important applications. Abstract : The mechanism of aggregation‐induced emission is revealed by monitoring real time structural evolution and dynamics of the electronic excited state. The formation of Woodward–Hoffmann cyclic intermediates as nonradiative relaxation pathway is observed in dilute solutions of tetraphenylethylene upon ultraviolet excitation. In solid state, the electronic excitation is preserved, and the molecule fluoresces efficiently.